Developing a tool for automated code review in ServiceNow - Vacula, Filip; Bruckner, Tomáš, 1974-; Perůtka, Lukáš; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2021)
Technical debt, code review and related concepts of software development are first explored and then applied to the specific case of GuideVision, a technical consultancy with sole focus on the ServiceNow platform. A tool for automated code review in the ServiceNow platform is developed as part of this paper and after more than 2 years of active use evaluated in a single case study. The study finds out that the tool provides value to the company by lowering the time to perform code review, increasing quality of delivered code, speeding up the development by minimizing handoffs between people and has five additional secondary benefits. However, there is potential for increased value if identified areas for improvement are addressed. The most impactful is universal use on all customer projects, which is currently limited due to security policies.
Vedoucí práce: Tomáš Bruckner
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: informační systémy a technologie [obor dipl. práce]; diplomové práce; master's theses